Gross anatomy and ultrasonographic images of the reproductive system of the Sumatran Rhinoceros (Dicerorhinus sumatrensis) - Zainal Zahari, Z.; Rosnina, Y.; Wahid, H.; Jainudeen, M.R. (Wiley, 2002)
The Sumatran rhinoceros (Dicerorhinus sumatrensis) is the smallest of all the rhino species. It is one of the rarest mammals in the world and is in imminent danger of extinction. A study was carried out on seven wild-caught females, three wild-caught males and one captive born female Sumatran rhinoceros at the Sumatran Rhinoceros Breeding Centre in Sungai Dusun, Selangor, Malaysia, beginning 1990. As a result of the paucity of scientific information on the reproductive biology of the Sumatran rhinoceros, this study was conducted to obtain information, which could assist in the captive breeding of this endangered and near extinct species. The anatomy of the reproductive system was based on two post-mortem specimens and transrectal real-time ultrasonography in six adult females. Genitalia of the Sumatran rhinoceros were similar to those of other species of rhinoceroses. The cervix consisted of several folds, the uterus was bicornuate with a short body and prominent horns and the ovaries were completely covered by the fimbriated end of the fallopian tube. The internal genitalia could be imaged by ultrasonography. The testes were located within a pendulous scrotum. Two lateral projections were located at the base of the penis. A well-defined process glandis was present at the tip of the penis. The accessory sex glands and the testes could be imaged by ultrasonography.